RELATIONSHIP BETWEEN RECLAMATION LAND COVER BASED ON THE NORMALIZED DIFFERENCE VEGETATION INDEX AND VOID WATER CHARACTERISTICS AT MELAWAN PANEL 2 - Gigih Anugrah Irfatongga; Harmin Sulistyaning Titah; Nur 'Izzati Ismail (Purifikasi, 2026)
Open-pit coal mining leaves post-mining pit lakes (voids) filled with rainwater and surface runoff, exhibiting complex physicochemical characteristics. This study analysed the relationship between reclamation land cover quality based on the Normalized Difference Vegetation Index (NDVI) and water quality characteristics of Void Melawan Panel 2, PT Kaltim Prima Coal, East Kutai Regency, East Kalimantan, Indonesia. The dynamics of reclamation land cover were assessed using multitemporal Sentinel-2 satellite imagery from 2020 to 2026 and classified into four NDVI categories: non-vegetation, low vegetation, moderate vegetation, and high vegetation. Water quality was evaluated based on pH, Total Suspended Solids (TSS), iron (Fe), and manganese (Mn) through purposive sampling at nine monitoring points across three depth zones (surface, middle, and bottom) during both dry and rainy seasons from 2024 to 2026. Spatial analysis was conducted using QGIS, trend analysis was performed using Kendall’s tau-b, and relationships among variables were assessed using Spearman correlation. The results showed that the proportion of moderate vegetation increased significantly from 18% to 54%, while the mean NDVI increased from 0.17 to 0.27 (τ = 0.851; p < 0.05). Void water quality characteristics remained relatively stable and complied with the standards stipulated in the Indonesian Ministerial Decree of Environment No. 113 of 2003. Spearman correlation analysis revealed a strong positive relationship between NDVI and pH (r = 0.690; p < 0.001) and a strong negative relationship between NDVI and Mn (r = −0.628; p < 0.001), whereas the relationships between NDVI and TSS and between NDVI and Fe were not statistically significant. These findings indicate that the development of reclamation vegetation within the catchment area is associated with the environmental stability of the void aquatic system.